Financial Stability of Islamic Banks of Bangladesh: An Empirical Study - Islam, Razeul; Md. Sumon, Shah; Ahmed, Raju; Yousuf, Md. (Journal of Islamic Finance, 2019)
This paper examines the financial stability of eight (8) full fledge Islamic banks in Bangladesh for the period of 2010 to 2017 using the technique of Z-score along with different financial ratios such as NPF Ratio, IDR Ratio and Liquidity Ratio that are widely accepted to assess the financial stability of Islamic banks. The relevant data are collected from the published annual reports of these Islamic banks. The finding of the paper reveals that most of the Islamic banks have lower Z-score in recent years and thus suggests that Islamic banks at present aren’t on the whole financially stable. The results of the study suggest that Islamic banks in Bangladesh are now experiencing higher IDR ratio which indicates these banks are making excessive financing. Although the NPF ratios for some Islamic banks are decreasing but the pace of this decrease is very low.